PERENCANAAN SUMBERDAYA MANUSIA YANG EFEKTIF: STRATEGI MENCAPAI KEUNGGULAN KOMPETITIF - Widajanti, Erni (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT Change covering: very business rate of change quickly with high uncertainty, increase of expense along with increase emulation pressure at profit margin, technological change very quickly resulting the increasing of request of membership will newly pass enable ness, training and education repeat, organization which progressively complex, slimmer organization, more level off and is flexible, change of demography the increasing multinational emulation and collaboration also multilateral relation result role of human resource (SDM) mount. This matter make SDM as source of excellence potential competitive because owned interested intellectuality, nature of, skill, personal character, and also cognate and intellectual process, cannot be imitated by other company. Keywords: planning SDM, excellence of competition